Family Support for Maternal Health and Child Care during the First 1,000 Days of a Child's Life: An Exploration of the Experiences of Urban Families - Wiradnyani, Luh Ade Ari; Khusun, Helda; L. Achadi, Endang; Ocviyanti, Dwiana (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2024)
This qualitative study examines the families' support regarding maternal health and child care toward mothers who demonstrated Good Compliance (GC) and Poor Compliance (PC) with nutrition interventions during the first 1,000 days of their child's life. The study employed an in-depth interview method to gather data from 20 fathers and 7 grandparents residing in Bogor City. The data were analyzed using a constant comparison approach between the GC and PC groups for each theme. The findings indicated that family members provided more specific support for child feeding than for maternal Iron-Folic Acid Supplementation (IFAS), given that the mothers encountered more difficulties on child feeding. Encouraging the mothers to continue taking IFA supplement despite their hesitance was predominantly reported by fathers in the GC fathers. Regarding child feeding, in addition to encouraging the child to eat and feeding them, the GC fathers often engaged in discussions with their wives. In contrast, the PC fathers rarely engaged in such discussions and were only consulted when their wives reported problem. Furthermore, fathers considered their wives to be more knowledgeable on these issues as fathers had limited time due to work commitment. Grandmothers primarily offered advice on child feeding based on their own experiences, sometimes providing less suitable advice for PC mothers. While fathers in both groups did not proactively seek information about maternal health and child care, the GC fathers were more likely to be encountered such information through discussions initiated by their wives, prompting them to pursue further reading. The interaction of fathers in both groups with health professionals only occurred during antenatal visits, with minimal communication. It is recommended that strategies be developed to engage family more highlight their crucial role in fostering a supportive environment for mothers. It is aslo advised that antenal visits be optimized and the Maternal and Child Health (MCH)handbook be utilized to raise awareness and enhance paternal involvement.